A multi-scale “morphological approach” for highly-filled particulate composites: evaluation in hyperelasticity and first application to viscohyperelasticity - Touboul, M.; Nadot-Martin, C.; Dragon, A.; Fanget, A. (Archives of Mechanics, 2007)
This article deals with a non-classical scale transition devoted, in the long-run, to the prediction of the nonlinear mechanical behavior of energetic composites. A geometrical and kinematical schematization of the microstructure is defined as a conspicuous starting point for further localization-homogenization procedure. Thus, salient information on the morphology and some intraphase heterogeneity are taken into account. The first results obtained in a finite strain context for a three-dimensional periodic microstructure are compared to the finite element solution. Furthermore, the ability of the methodology to deal with viscohyperelasticity in a direct manner is illustrated. This is a significant step towards efficient mastery of the scale transition for viscoelastic aggregates, whose inherent characteristic lies in space/time local interactions and relative “long-memory” effect.